Вплив електронного опромінення на оптичні властивості плівок нанокристалічного SiC на підкладках із монокристала Al2O3 - Semenov, O. V.; Lopin, A. V.; Boriskin, V. N. (PE "Politekhperiodika", Book and Journal Publishers, 2017)
It was studied the effect of irradiation with high-energy (10 MeV) electrons on the optical properties of nanocrystalline carbide film system silicon / sapphire substrates in a wide range of fluences of 5·1014 to 2·1020 cm–2 and subsequent annealing in vacuum in the range of 200—1200°C. It was found that radiation-induced changes in the optical properties of nc SiC films are primarily manifested in the UV region of the spectrum associated with interband transitions, as well as in the region of the spectrum due to the absorption of intrinsic defects and disordered regions. It was established in the beginning of the annealing of defects in irradiated films has been observed at 200°C, which indicates the high concentration of carbon vacancies with the lowest activation energy. Significant changes in the optical properties of sapphire begin at fluence 5·1017 cm–2, which should be considered when using these materials under conditions of intense radiation impact.